A Cisplatin Derivative that Inhibits Collagen Fibril‐Formation in vitro. (5th November 2014) - Zenda, Miyu; Yasui, Hiroyuki; Oishi, Shinya; Masuda, Ryo; Fujii, Nobutaka; Koide, Takaki
<x xml:space="preserve">Abstract</x> Using an in vitro random screening of small‐molecule compounds, we discovered cis‐diamminedichloroplatinum(II) (cisplatin), an anticancer agent, as a potential inhibitor of collagen fibril‐formation. The inhibitory effect was found only when cisplatin was dissolved in dimethylsulphoxide (DMSO), indicating that the active species were cisplatin derivatives formed in the DMSO solution. The cisplatin derivatives inhibited the formation of collagen fibrils in vitro without affecting the triple‐helical conformation of the collagen molecules. Incubation with the cisplatin solution in DMSO also inhibited in situ deposition of collagen fibrils in a human umbilical vein endothelial cell (HUVEC) culture. In addition, the derivatization of cisplatin in DMSO abolished the cytotoxicity of the original compound. The platinum complex was further revealed to interact with specific sites on the collagen triple helix, and the binding sites were suggested to contain His and/or Met residues. Mass spectrometry analysis of the cisplatin solution in DMSO and a structure–activity relationship study strongly suggested that the active compound is [Pt(NH3)2(Cl)(DMSO)]+. This platinum complex will be useful for investigating molecular mechanisms of collagen self‐assembly and for drug development for the treatment of fibrotic diseases.